Lyme Disease: Is It or Is It Not? - BL Johnston; JM Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
This past summer, Lyme disease was the topic of a Focus section in the Globe and Mail (1). In this section, the reporter described her experience of having physicians unable and then unwilling to diagnose her symptoms of "skin on fire, dizziness and chest pains, twitching muscles, and trouble keeping balance" as Lyme disease following a tick bite three years previously on Prince Edward Island. She reported finding support for her diagnosis after obtaining a positive test from a California laboratory and after seeing approximately 20 physicians. In her article, she speaks to the controversy surrounding the diagnosis and treatment of Lyme disease, and the tension it creates between those who believe they have it and the physicians they see.